Luto como uma crise familiar: uma abordagem terapêutica e preventiva - Franco, Maria Helena Pereira (1992)
This work deals with a qualitative research on bereavement in the family. Its objectives were to study and analyse aspects that influence on the family as a system, without disconsidering the impact for each one of the members. Bereavement is a crisis experience and thus was dealt with. Case-studies method was used and the therapeutic sessions of bereaved families were analysed. From the technical point of view, resources from brief family therapy in the systhemic approuch were used, together with rituals, with the specific aim of the objectives of the therapy: shared acknowledgment about the reality of loss; sharing the loss experience and its contextualization; reorganization of the family system and reinvestment in new relationships and life objectives. Changes in the direction of reaching the objectives were observed in the studied families. This research came to the conclusion that rituals are a positive tool for the psychotherapy of bereaved families,this if these families had not been previously over-ritualized. If is the case, there is a risk of rituals being used with anti-therapeutic aims, in order to maintain what had been already stablished, in stead of changing it. The research also came to the conclusion that it is possible to work ecosystemically with the family, even if only one person is present at the sessions. The various bereavement situations in the studied families led to a wide discussion about the results. The preventive aspect was delt with as far as trigenerational aspects, and effects of pathologic bereavement were concerned, and also raised subjects such as reference to somatic complaints, learning disabilities or behaviour disturbances in children. It also raised subjects to be reflected upon, related to the taboo of death, as well as to the necessity of training for health personnel, mainly those envolved with the facing of death